Innovation in Assurance: Doing more, and more effectively, with less - FOO, See Liang (Institutional Knowledge at Singapore Management University, 2016)
Back in early 2013, Jimmy Ng, the new head of Group Audit at DBS received an urgent call from Kelvin Lam, Country Head of Taiwan Audit, requesting increasing Taiwan’s audit headcount by ten for mandatory audits required by the Financial Supervisory Commission in Taiwan. However, Ng was very sensitive about allocating more headcount to Taiwan, especially for compliance activities that consumed extensive resources. On the other hand, as DBS Taiwan had grown to 43 branches, the volume of mandatory audits kept increasing for the bank – all of its branches, business and support units were subject to two mandatory audits per year. In view of the cumbersome audit work and the serious consequence of compliance failure, Ng understood that providing more headcount would be of no help in the long run. A fundamental business strategy was required to rethink the auditing process to make it less volume sensitive. The case describes a successful strategic transformation on the audit process at DBS. It provides a practical understanding of the meaning of continuous assurance and its significance in the context of sound management and governance. It covers the motivations to launch continuous assurance, the development process, the potential benefits, and the challenges and lessons learned.